2012
DOI: 10.1126/science.1223602
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanics of Cardiac Myosin-Binding Protein C in Native Thick Filaments

Abstract: The heart's pumping capacity results from highly regulated interactions of actomyosin molecular motors. Mutations in the gene for a potential regulator of these motors, cardiac myosin binding protein-C (cMyBP-C), cause hypertrophic cardiomyopathy. However, cMyBP-C's ability to modulate cardiac contractility is not well understood. Using single particle fluorescence imaging techniques, transgenic protein expression, proteomics, and modeling, we found that cMyBP-C slowed actomyosin motion generation in native ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
244
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(270 citation statements)
references
References 33 publications
23
244
0
3
Order By: Relevance
“…In addition to the thin filament activating effects of cMyBP-C at low Ca 2+ , cMyBP-C also governs contractility, as evidenced by enhanced unloaded cardiac muscle shortening velocities in cMyBP-C null mice (43). The inhibition of velocity in the presence of cMyBP-C occurs through cMyBP-C's N terminus, as observed previously by ourselves and others (16,19,20,50) and confirmed here (Fig. 6).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition to the thin filament activating effects of cMyBP-C at low Ca 2+ , cMyBP-C also governs contractility, as evidenced by enhanced unloaded cardiac muscle shortening velocities in cMyBP-C null mice (43). The inhibition of velocity in the presence of cMyBP-C occurs through cMyBP-C's N terminus, as observed previously by ourselves and others (16,19,20,50) and confirmed here (Fig. 6).…”
Section: Discussionsupporting
confidence: 71%
“…The cMyBP-C domains primarily involved in binding actin appear to be the C1 and M-domains (9,15,16,20), although there is evidence that C0 may be important (10,14). Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Using this assay, we showed that the sliding velocity of bare F-actin filaments was slowed within the C-zone of thick filaments and that the degree of slowing was reduced by phosphorylation of the four serines within the M-domain (21). Next, we examined the motion of native thin filaments containing the calcium-regulatory troponin-tropomyosin complex over native thick filaments.…”
Section: Significancementioning
confidence: 99%
“…filaments (21,23). The actin filaments used in this assay are short 250-nm shards, which allow independent probing of thick filament areas with and without cMyBP-C (the C-and D-zones, respectively) (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation